The Effectiveness of Real Science Mask with QR Code on Students' Problem-Solving Skills and Scientific Literacy - Savitri, E. N.; Amalia, A. V.; Prabowo, S. A.; Rahmadani, O. E. P.; Kholidah, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study aims to determine the effectiveness of Real Science Mask with QR Code on students' problem-solving skills and scientific literacy. This research is a type of experimental research that uses the Pretest Posttest Control Group Design model. The subjects of this study were students in the Integrated Science Education study program for the academic year 2020/2021 of Universitas Negeri Semarang. The sample from the population was divided into experimental class and control class. The observation instrument used an observation sheet based on the assessment indicators of students' activities during learning. Data analysis in this study used quantitative descriptive analysis, where each average value is described in each aspect of the assessment based on indicators. The results showed that the experimental class that applied the Real Science Mask with QR Code had the highest average score of Problem-Solving skills in the assessment aspect of discussing the suitability of scientific phenomena with a score of 9.4 and scientific literacy on the aspect of student assessment in seeking scientific references with a score of 8.8. The posttest results obtained a t-count value of 8,951 with df = 16, consulted with the t-table value at a significance level of 5%, and df = 16 obtained 2,120. These results indicate that the value of t-count is greater than the t-table value (8,951 > 2,120) it means that there is a significant difference between the experimental and control classes. Furthermore, the average of these two aspects of the assessment is higher when compared to the control class. These results indicate that the Real Science Mask with QR Code is effective in improving students' problem-solving skills and scientific literacy.